2009
DOI: 10.1080/02713680902919532
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Pharmacokinetics of AzaSite Xtra—2% Azithromycin Formulated in a DuraSite Delivery System

Abstract: The PK/PD profile of 2% azithromycin suggests efficacy against common causative bacteria with just one dose per day for three days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Comparing our rabbit tear concentrations at 0.5-12 h with those of Amar et al (2008) and Si et al (2009), we believe, with twice-daily administrations of 1% (w/v) ATM in situ gel in the eyes, significant antibacterial ATM levels remain for a long period of time in the tears and in the conjunctiva.…”
Section: In Vivo Resident Evaluationmentioning
confidence: 79%
See 1 more Smart Citation
“…Comparing our rabbit tear concentrations at 0.5-12 h with those of Amar et al (2008) and Si et al (2009), we believe, with twice-daily administrations of 1% (w/v) ATM in situ gel in the eyes, significant antibacterial ATM levels remain for a long period of time in the tears and in the conjunctiva.…”
Section: In Vivo Resident Evaluationmentioning
confidence: 79%
“…However, others have demonstrated that dosing of 1.5 or 2% ATM achieved adequate conjunctiva concentrations to eradicate ATM-susceptible bacteria in a rabbit model of experimental keratitis (Amar et al, 2008;Si et al, 2009). Comparing our rabbit tear concentrations at 0.5-12 h with those of Amar et al (2008) and Si et al (2009), we believe, with twice-daily administrations of 1% (w/v) ATM in situ gel in the eyes, significant antibacterial ATM levels remain for a long period of time in the tears and in the conjunctiva.…”
Section: In Vivo Resident Evaluationmentioning
confidence: 99%
“…Recently, the pharmacokinetics of a 2% ocular solution of azithromycin in DuraSite (AzaSite Xtra™) was analysed in forty-two male pigmented rabbits 30. Twenty-four hours after administration of a single drop, corneal and conjunctival concentrations exceeded the minimum inhibitory concentration breakpoint for the most common causative pathogens of bacterial conjunctivitis by 3.5- and 5.8-fold, respectively; whereas the plasma levels were four to five orders of magnitude lower than ocular tissue levels.…”
Section: Pharmacokinetics Of Azithromycinmentioning
confidence: 99%
“…The studies on formulations give insight into how this new preparation is thought to work. 29,30 Azithromycin is hydrophobic and is sparingly soluble in water at neutral pH. Aqueous preparations of azithromycin for topical administration to the eye are therefore labile at room temperature and can degrade.…”
Section: Formulationmentioning
confidence: 99%